Molding slag prepared from gasified fine slag carbon-rich component and solid waste fan blade in cooperation and preparation method
By mixing gasified fine slag, composite binder and waste fan blades in a specific proportion and modifying and processing, a slag with high cold and heat strength is prepared, which solves the problems of insufficient resource utilization and environmental pollution in the existing technology, and achieves the effects of resource recycling and environmental protection.
Patent Information
- Application Number
- CN202411231029.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to effectively utilize gasified fine slag and waste fan blades, resulting in environmental pollution and waste of resources. At the same time, there are problems of exhaust pollution and high costs during the thermal cracking recycling process.
By mixing the gasified fine slag, composite binder and waste fan blades in a specific proportion, and modifying them by sodium hydroxide solution, then processing at 50-70°C for 6 hours, cold-pressed molding, curing and insulated, and finally molding with high cold and heat strength was prepared.
The resource recycling and utilization of gasified fine slag and waste fan blades is realized, environmental pollution is reduced, exhaust gas pollution is avoided in thermal cracking, and the hot and cold strength of the slag is improved, which is suitable for the reuse of gasification of fixed beds at normal pressure.
Smart Images

Figure CN119750960A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a slag mold prepared by cooperating between carbon-rich components of gasified fine slag and solid waste fan blades and a preparation method thereof, belonging to the technical field of resource utilization. Background Art
[0002] During the entrained-bed gasification process, two types of solid waste, gasification coarse slag and gasification fine slag, are produced. The coarse slag is discharged from the gasifier slag outlet, accounting for 60% to 80% of the total slag discharge; the fine slag is produced in the coal gas dust removal device, accounting for 20% to 40% of the total slag discharge. At present, most of the gasification fine slag is disposed of in the form of open-air dumping or landfill, which not only releases harmful gases, but also causes dust pollution. At the same time, with the rain, the heavy metals leached from the gasification fine slag will also pollute the land and water bodies. The landfilled gasification fine slag has laid hidden dangers for future environmental problems. The gasification fine slag can be separated into carbon-rich components and high-ash components by carbon-ash separation. The carbon-rich component can be used for boiler blending and preparation of high-value-added products, and the high-ash component can be used in cement and concrete. The structural characteristics of carbon ash melting and bonding seriously restrict the cyclic blending and high-value utilization, and due to technical and cost issues, there is still a long way to go before industrialization. High-yield gasification slag replacing too much cement concrete will lead to loose product structure and reduced mechanical properties.
[0003] In addition, the rapid development of wind power generation has led to an increase in the number of wind turbine blades retired in China year by year. The treatment of discarded wind turbine blades has also become a hot topic in the field of environmental protection. The commonly used method for recycling waste wind turbine blades is thermal cracking. After the waste wind turbine blades are crushed, they are subjected to thermal cracking reaction in a set atmosphere at a temperature range of 300-550°C. However, there are many problems in the recycling process. Incomplete thermal cracking of the resin in the waste wind turbine blades will lead to insufficient production of pyrolysis oil and pyrolysis gas, and will also produce toxic substances, which will not only make it difficult to collect tail gas, but also threaten human health. When pyrolyzing in an air atmosphere, the particles containing resin with very small particle size in the pyrolysis reactor are at risk of explosion. If pyrolysis is carried out in an inert gas atmosphere, the recycling cost of waste wind turbine blades will be greatly increased.
[0004] Studies have shown that the residual carbon in gasification fine slag has low activity and poor plasticity, and a suitable binder needs to be selected for the molding of carbon-rich fine slag. At the same time, since the main components of fan blades are glass fiber, epoxy resin, etc. Glass fiber has high mechanical strength and can be used as a reinforcing material. Epoxy resin has good adhesion, is suitable for the preparation of thermosetting materials, and can improve the thermal stability of materials. Therefore, this study aims to solve the problem of synergistic preparation of molded slag from carbon-rich components of gasification fine slag and solid waste fan blades and recycling them as resources. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a slag mold and a preparation method for the coordinated preparation of carbon-rich components of gasified fine slag and solid waste fan blades, which has the advantage of realizing the resource recycling of carbon-rich components of gasified fine slag and solid waste fan blades.
[0006] The above-mentioned inventive object of the present invention is achieved through the following technical scheme: a mold slag prepared by cooperating with the carbon-rich component of gasified fine slag and solid waste fan blades, which is composed of the following raw materials in weight: carbon-rich fine slag: composite binder: fan blade = 71-83:15-25:2-4, the composite binder is prepared by mixing industrial starch, bentonite and humic acid in a mass ratio of 5:3:2, the carbon-rich fine slag, composite binder and fan blades are mixed and modified by sodium hydroxide solution, the obtained product is treated at 50-70°C for 6h, and is formed into a mold slag by cold pressing, curing and insulation.
[0007] Preferably, it is composed of the following raw materials in weight: carbon-rich fine slag: composite binder: fan blade = 77:20:3.
[0008] Preferably, the concentration of the sodium hydroxide solution is 1 mol / L.
[0009] Preferably, the mass ratio of the carbon-rich fine slag to 1 mol / L sodium hydroxide solution is 1:0.8-1.2.
[0010] Preferably, the particle size of the carbon-rich fine slag is 30-180 mesh.
[0011] Preferably, the particle size of the fan blades is 80-120 mesh.
[0012] Preferably, the pressure value of the cold press forming is 8-15 MPa.
[0013] Preferably, the method further comprises curing the slag after cold pressing at 100° C. for 3 hours.
[0014] Preferably, the method further comprises placing the solidified slag at 200° C. for 4 hours.
[0015] Also disclosed is a method for preparing the above-mentioned slag, comprising the following steps:
[0016] a. The entrained flow carbon-rich fine slag is flotated and screened to obtain a component with a particle size of 30-180 mesh;
[0017] b. Mill the fan blades in a ball mill for 10 minutes and sieve out the 80-120 mesh components;
[0018] c. Weigh the screened carbon-rich fine slag, fan blades, composite binder, and 1 mol / L sodium hydroxide solution according to weight and mix them thoroughly;
[0019] d. The mixed solution was placed at 50-70°C for 6 hours;
[0020] e. cold pressing the mixture under a pressure of 8-15 MPa;
[0021] f. The cold-pressed mixture was cured at 100°C for 3h;
[0022] g. The solidified mixture is kept at 200° C. for 4 hours to obtain the slag.
[0023] In summary, the present invention includes at least one of the following beneficial technical effects:
[0024] 1. The method for preparing molded slag disclosed in the present invention can simultaneously combine two solid wastes, namely, gasified fine slag and waste fan blades, to realize resource utilization of solid waste and reduce the impact on the environment;
[0025] 2. The method for preparing molded slag disclosed in the present invention can avoid the generation of highly toxic tail gas and environmental pollution when recycling waste fan blades by thermal cracking;
[0026] 3. The slag prepared by the method disclosed in the present invention has strong cold strength and hot strength, and can be reused during atmospheric pressure fixed bed gasification, thereby realizing solid waste recycling. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a diagram showing the cold compression strength and hot strength of the slag prepared in Example 1 of the present invention;
[0028] Figure 2 This is a diagram showing the cold compression strength and hot strength of the slag prepared in Example 2 of the present invention;
[0029] Figure 3 This is a diagram showing the cold compression strength and hot strength of the slag prepared in Example 3 of the present invention;
[0030] Figure 4 This is a diagram showing the cold compression strength and hot strength of the slag prepared in Example 4 of the present invention;
[0031] Figure 5 This is a diagram showing the cold compression strength and hot strength of the slag prepared in Example 5 of the present invention;
[0032] Figure 6 This is a diagram showing the cold compression strength and hot strength of the slag prepared in Example 6 of the present invention. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiment of the present application clearer, the technical scheme of the embodiment of the present application will be clearly and completely described in conjunction with the drawings of the embodiment of the present application. Obviously, the described embodiment is a part of the embodiment of the present application, not all of the embodiments. Based on the described embodiment of the present application, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of this application.
[0034] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0035] Embodiment 1:
[0036] The fine slag from the entrained-bed gasification is separated under the action of the water flow of the spiral separator. The carbon with low density flows along the water on the outside of the spiral, and the ash with high density sinks on the inside. The carbon-rich components are separated, and the components with a particle size of 30-180 mesh are floated and screened.
[0037] The fan blades were crushed, and the crushed fan blades were placed in a ball mill for 10 minutes, and the 80-120 mesh components were sieved out;
[0038] The screened carbon-rich fine slag is fully mixed with the composite binder in a weight ratio of 75:25. In addition, in this embodiment, the components of the composite binder used are: industrial starch: bentonite: humic acid = 5:3:2;
[0039] The mixed mixture was placed in a 1 mol / L sodium hydroxide solution and mixed at a ratio of 1:0.8;
[0040] The mixed solution was placed at 50-70°C for 6 hours;
[0041] The mixture is placed under a pressure of 8-15 MPa for cold pressing, solidified at 100°C for 3 hours, and finally kept at 200°C for 4 hours to obtain a mold slag.
[0042] The obtained slag is subjected to cold compression strength test according to MT / T748-2007 "Test Method for Cold Compression Strength of Industrial Coal Shapes" and hot strength test according to MT / T1073-2008 "Test Method for Hot Strength of Industrial Coal Shapes". Figure 1 As shown in the results, it can be seen that the cold pressing strength of the slag prepared in this embodiment is 2.23MPa, and the hot strength is 1.31MPa.
[0043] Embodiment 2:
[0044] The fine slag from the entrained-bed gasification is separated under the action of the water flow of the spiral separator. The carbon with low density flows along the water on the outside of the spiral, and the ash with high density sinks on the inside. The carbon-rich components are separated, and the components with a particle size of 30-180 mesh are floated and screened.
[0045] The fan blades were crushed, and the crushed fan blades were placed in a ball mill for 10 minutes, and the 80-120 mesh components were sieved out;
[0046] The screened carbon-rich fine slag, fan blades and composite binder are fully mixed in a weight ratio of 82:3:15. In addition, in this embodiment, the components of the composite binder used are: industrial starch: bentonite: humic acid = 5:3:2;
[0047] The mixed mixture was placed in a 1 mol / L sodium hydroxide solution and mixed at a ratio of 1:0.8;
[0048] The mixed solution was placed at 50-70°C for 6 hours;
[0049] The mixture is placed under a pressure of 8-15 MPa for cold pressing, solidified at 100°C for 3 hours, and finally kept at 200°C for 4 hours to obtain a mold slag.
[0050] The obtained slag is subjected to cold compression strength test according to MT / T748-2007 "Test Method for Cold Compression Strength of Industrial Coal Shapes" and hot strength test according to MT / T1073-2008 "Test Method for Hot Strength of Industrial Coal Shapes". Figure 2 As shown in the results, it can be seen that the cold pressing strength of the slag prepared in this embodiment is 2.65MPa, and the hot strength is 1.42MPa.
[0051] Embodiment 3:
[0052] The fine slag from the entrained-bed gasification is separated under the action of the water flow of the spiral separator. The carbon with low density flows along the water on the outside of the spiral, and the ash with high density sinks on the inside. The carbon-rich components are separated, and the components with a particle size of 30-180 mesh are floated and screened.
[0053] The fan blades were crushed, and the crushed fan blades were placed in a ball mill for 10 minutes, and the 80-120 mesh components were sieved out;
[0054] The screened carbon-rich fine slag, fan blades and composite binder are fully mixed in a weight ratio of 77:3:20. In addition, in this embodiment, the components of the composite binder used are: industrial starch: bentonite: humic acid = 5:3:2;
[0055] The mixed mixture was placed in a 1 mol / L sodium hydroxide solution and mixed at a ratio of 1:0.8;
[0056] The mixed solution was placed at 50-70°C for 6 hours;
[0057] The mixture is placed under a pressure of 8-15 MPa for cold pressing, solidified at 100°C for 3 hours, and finally kept at 200°C for 4 hours to obtain a mold slag.
[0058] The obtained slag is subjected to cold compression strength test according to MT / T748-2007 "Test Method for Cold Compression Strength of Industrial Coal Shapes" and hot strength test according to MT / T1073-2008 "Test Method for Hot Strength of Industrial Coal Shapes". Figure 3 As shown in the results, it can be seen that the cold pressing strength of the slag prepared in this embodiment is 4.48MPa, and the hot strength is 1.78MPa.
[0059] Embodiment 4:
[0060] The fine slag from the entrained-bed gasification is separated under the action of the water flow of the spiral separator. The carbon with low density flows along the water on the outside of the spiral, and the ash with high density sinks on the inside. The carbon-rich components are separated, and the components with a particle size of 30-180 mesh are floated and screened.
[0061] The fan blades were crushed, and the crushed fan blades were placed in a ball mill for 10 minutes, and the 80-120 mesh components were sieved out;
[0062] The screened carbon-rich fine slag, fan blades and composite binder are fully mixed in a weight ratio of 72:3:25. In addition, in this embodiment, the components of the composite binder used are: industrial starch: bentonite: humic acid = 5:3:2;
[0063] The mixed mixture was placed in a 1 mol / L sodium hydroxide solution and mixed at a ratio of 1:0.8;
[0064] The mixed solution was placed at 50-70°C for 6 hours;
[0065] The mixture is placed under a pressure of 8-15 MPa for cold pressing, solidified at 100°C for 3 hours, and finally kept at 200°C for 4 hours to obtain a mold slag.
[0066] The obtained slag is subjected to cold compression strength test according to MT / T748-2007 "Test Method for Cold Compression Strength of Industrial Coal Shapes" and hot strength test according to MT / T1073-2008 "Test Method for Hot Strength of Industrial Coal Shapes". Figure 4 As shown in the results, it can be seen that the cold pressing strength of the slag prepared in this embodiment is 5.49 MPa, and the hot strength is 2.10 MPa.
[0067] Embodiment 5:
[0068] The fine slag from the entrained-bed gasification is separated under the action of the water flow of the spiral separator. The carbon with low density flows along the water on the outside of the spiral, and the ash with high density sinks on the inside. The carbon-rich components are separated, and the components with a particle size of 30-180 mesh are floated and screened.
[0069] The fan blades were crushed, and the crushed fan blades were placed in a ball mill for 10 minutes, and the 80-120 mesh components were sieved out;
[0070] The screened carbon-rich fine slag, fan blades and composite binder are fully mixed in a weight ratio of 78:2:20. In addition, in this embodiment, the components of the composite binder used are: industrial starch: bentonite: humic acid = 5:3:2;
[0071] The mixed mixture was placed in a 1 mol / L sodium hydroxide solution and mixed at a ratio of 1:0.8;
[0072] The mixed solution was placed at 50-70°C for 6 hours;
[0073] The mixture is placed under a pressure of 8-15 MPa for cold pressing, solidified at 100°C for 3 hours, and finally kept at 200°C for 4 hours to obtain a mold slag.
[0074] The obtained slag is subjected to cold compression strength test according to MT / T748-2007 "Test Method for Cold Compression Strength of Industrial Coal Shapes" and hot strength test according to MT / T1073-2008 "Test Method for Hot Strength of Industrial Coal Shapes". Figure 5 As shown in the results, it can be seen that the cold pressing strength of the slag prepared in this embodiment is 3.63MPa, and the hot strength is 1.69MPa.
[0075] Embodiment 6:
[0076] The fine slag from the entrained-bed gasification is separated under the action of the water flow of the spiral separator. The carbon with low density flows along the water on the outside of the spiral, and the ash with high density sinks on the inside. The carbon-rich components are separated, and the components with a particle size of 30-180 mesh are floated and screened.
[0077] The fan blades were crushed, and the crushed fan blades were placed in a ball mill for 10 minutes, and the 80-120 mesh components were sieved out;
[0078] The screened carbon-rich fine slag, fan blades and composite binder are fully mixed in a weight ratio of 76:4:20. In addition, in this embodiment, the components of the composite binder used are: industrial starch: bentonite: humic acid = 5:3:2;
[0079] The mixed mixture was placed in a 1 mol / L sodium hydroxide solution and mixed at a ratio of 1:0.8;
[0080] The mixed solution was placed at 50-70°C for 6 hours;
[0081] The mixture is placed under a pressure of 8-15 MPa for cold pressing, solidified at 100°C for 3 hours, and finally kept at 200°C for 4 hours to obtain a mold slag.
[0082] The obtained slag is subjected to cold compression strength test according to MT / T748-2007 "Test Method for Cold Compression Strength of Industrial Coal Shapes" and hot strength test according to MT / T1073-2008 "Test Method for Hot Strength of Industrial Coal Shapes". Figure 6 As shown in the results, it can be seen that the cold pressing strength of the slag prepared in this embodiment is 5.00MPa, and the hot strength is 2.08MPa.
[0083] In summary: The test data of Examples 1-6 are shown in the following table:
[0084]
[0085] In summary, it can be obtained from Examples 1 and 3 that, under the same proportion of composite binder addition, the cold pressing strength of the slag prepared in Example 3 containing waste fan blades is 2.25 MPa higher than that of the slag prepared in Example 1, which is nearly 1 times higher. The results show that by adding waste fan blades, the cold pressing strength of the slag can be improved, thereby ensuring the durability of the slag during storage, transportation and use; and the thermal strength of the slag prepared in Example 3 is 0.47 MPa higher than that of the slag prepared in Example 1, which is 0.36 times higher. This shows that after adding waste fan blades, the thermal strength and carbonization degree of the slag can be improved to meet the conditions of fixed bed gasification at normal pressure, and the full utilization of resources can be reflected.
[0086] It can be seen from Examples 2-4 that when the weight fraction of the waste is at a constant value, and when the weight fraction of the composite binder is at 15, 20, and 25, the cold pressing strength and thermal strength of the prepared slag are improved. Therefore, in the present application, by using a composite binder prepared by using industrial starch, bentonite, and humic acid in a mass fraction of 5:3:2 and combining it with waste fan blades, the cold pressing strength and thermal strength of the prepared slag can be improved.
[0087] It can be seen from Examples 3, 5, and 6 that when the weight fraction of the composite binder is at a constant value, the cold pressing strength and hot strength of the mold slag prepared by adding waste fan blades with weight fractions of 3, 2, and 4 are improved. Therefore, in the present application, by using a composite binder prepared by industrial starch, bentonite, and humic acid in a mass fraction of 5:3:2 and combining it with waste fan blades, and by increasing the amount of waste fan blades added, the cold pressing strength and hot strength of the prepared mold slag can be significantly improved.
[0088] The embodiments of this specific implementation method are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A slag mold prepared by synergistically using carbon-rich components of gasified fine slag and solid waste fan blades, characterized in that: The composition is composed of the following raw materials by weight: carbon-rich fine slag: composite binder: fan blade = 71-83: 15-25: 2-4, The composite binder is prepared by mixing industrial starch, bentonite and humic acid in a mass ratio of 5:3:
2. The carbon-rich fine slag, the composite binder and the fan blades are mixed and modified by a sodium hydroxide solution, and the obtained product is treated at 50-70° C. for 6 hours, and is formed into molded slag by cold pressing, curing and heat preservation.
2. The molded slag prepared by synergistically using carbon-rich components of gasified fine slag and solid waste blower blades according to claim 1, characterized in that: The composition is composed of the following raw materials by weight: carbon-rich fine slag: composite binder: fan blade = 77:20:
3.
3. The molded slag prepared by synergistically using carbon-rich components of gasified fine slag and solid waste blower blades according to claim 1 or 2, characterized in that: The concentration of the sodium hydroxide solution is 1 mol / L.
4. The molded slag prepared by synergistically using carbon-rich components of gasified fine slag and solid waste blower blades according to claim 3, characterized in that: The mass ratio of the carbon-rich fine slag to 1 mol / L sodium hydroxide solution is 1:0.8-1.
2.
5. The molded slag prepared by synergistically using carbon-rich components of gasified fine slag and solid waste blower blades according to claim 1, characterized in that: The particle size of the carbon-rich fine slag is 30-180 meshes.
6. The molded slag prepared by synergistically using carbon-rich components of gasified fine slag and solid waste blower blades according to claim 1, characterized in that: The particle size of the fan blades is 80-120 meshes.
7. The molded slag prepared by synergistically using carbon-rich components of gasified fine slag and solid waste blower blades according to claim 1, characterized in that: The pressure value of the cold pressing is 8-15MPa.
8. The molded slag prepared by synergistically using carbon-rich components of gasified fine slag and solid waste blower blades according to claim 7, characterized in that: The curing is to place the cold-pressed mixture at 100° C. for curing for 3 hours.
9. The slag mold prepared by cooperating between the carbon-rich components of gasified fine slag and solid waste blower blades and the preparation method according to claim 8, characterized in that: The heat preservation is to place the solidified mixture at 200° C. and keep it for 4 hours.
10. A method for preparing the mold slag according to any one of claims 1 to 9, characterized in that: The following steps are involved: a. flotation of the carbon-rich fine slag from the entrained flow to obtain a component with a particle size of 30-180 mesh; b. Mill the fan blades in a ball mill for 10 minutes and sieve out the 80-120 mesh components; c. Weigh the screened carbon-rich fine slag, fan blades, composite binder, and 1 mol / L sodium hydroxide solution according to weight and mix them thoroughly; d. The mixed solution was placed at 50-70°C for 6 hours; e. cold pressing the mixture under a pressure of 8-15 MPa; f. The cold-pressed mixture was cured at 100°C for 3h; g. The solidified mixture is kept at 200° C. for 4 hours to obtain the slag.